Association between depressive symptoms and adherence among adolescents living with HIV in the Republic of Congo: A cross sectional study. Issue 35 (28th August 2020) - Ekat, Martin Herbas; Yotebieng, Marcel; Leroy, Valériane; Mpody, Christian; Diafouka, Merlin; Loubaki, Gilbert; Nsondé, Dominique Mahambou –; Ossibi Ibara, Bienvenu Rolland; Bernard, Charlotte; Sabin, Caroline; Becquet, Renaud
Abstract : Abstract: The increasing availability of antiretroviral therapy (ART) worldwide is yet to result in decreasing HIV-related mortality among adolescents (10–19 years old) living with HIV (ALHIV) in part because of poor adherence. the poor adherence might itself be due to high level of depression. We assess the prevalence of depressive symptomatology and it's associated with adherence among ALHIV receiving ART care in Brazzaville and Pointe Noire, Republic of Congo (RoC). Adolescents aged 10 to 19 years, on antiretroviral therapy (ART), followed in the two Ambulatory Treatment Centers (ATC) in Brazzaville and Pointe Noire, RoC were included in this cross-sectional study. From April 19 to July 9, 2018, participants were administered face to face interviews using a standardized questionnaire that included the nine-item Patient Health Questionnaire (PHQ-9). Participants who reported failing to take their ART more than twice in the 7 days preceding the interview were classified as non-adherent. Bivariate and multivariable log-binomial models were used to estimate the prevalence ratio (PR) and 95% confidence interval (95%CI) assessing the strength of association between predictors and presence of depressive symptoms (PHQ-9 score ≥9). Overall, 135 adolescents represented 50% of ALHIV in active care at the 2 clinics were interviewed. Of those, 67 (50%) were male, 81 (60%) were 15 to 19 years old, 124 (95%) had been perinatally infected, and 71 (53%) knew their HIV status. Depressive symptoms were present in 52 (39%) participants and 78 (58%) were adherent. In univariate analyses, the prevalence of depressive symptoms was relative higher among participants who were not adherent compared to those who were (73% vs 33%; PR: 2.20 [95%CI: 1.42–3.41]). In multivariate analysis, after adjustment for report of been sexually active, alcohol drinking, age category (10–14 and 15–19), not in school, loss of both parents, the association between depression and adherence was strengthened (PR: 2.06 [95%CI: 1.23–3.45]). The prevalence of depressive symptoms in adolescents living with HIV is high and was strongly associated with poor adherence even after adjustment of potential confounders. Efforts to scale-up access to screening and management of depression among ALHIV in sub-Saharan is needed for them to realize the full of ART.